EFFORTS TO IMPROVE THE ABILITY OF READING EARLY AGE CHILDREN THROUGH THE METHOD OF SINGING - Wawa Wartini (IKIP Siliwangi Bandung, 2019)
Language is a very important tool in the child's life, because with the language of children can communicate with others, the language aspect developed is reading in early childhood. Early reading can be said of the early ability to pass the child in the process of mastering the ability to read thoroughly. This encourages researchers to conduct a study on efforts to improve early childhood reading skills in Paud Sri Rejeki in Rw 06 Rt 03 Setiamanah village, Cimahi district, Central Cimahi city. The research is based on the problems found in Paud Sri Rejeki Rw 06 group B that is the ability to read the children who mostly are in the less category. The purpose of this research is to know the ability of children to read early before, during learning process, and result of reading ability of early child after using method of singing. The method used is descriptive study with qualitative approach. Subjects in this study were students Paud Sri Rejeki Rw 06 Cimahi which amounted to 5 people. The data collected is data of observation, interview and documentation study. The results showed that the use of singing method can improve reading ability of early child so that children can recognize letters, recognize words, and know the sentence. In other words, the method of singing can increase interest in reading early childhood.